2021
DOI: 10.1155/2021/6678067
|View full text |Cite
|
Sign up to set email alerts
|

Human Acquired Aplastic Anemia Patients’ Bone-Marrow-Derived Mesenchymal Stem Cells Are Not Influenced by Hematopoietic Compartment and Maintain Stemness and Immune Properties

Abstract: Background and Objective. Acquired aplastic anemia (aAA) is a bone marrow failure disorder characterized by pancytopenia and bone marrow aplasia. Bone marrow Mesenchymal Stem Cells (BM-MSCs) are an important component of BM microenvironment, associated with hematopoietic and immune homeostasis. Any alterations in BM microenvironment can disrupt the normal functioning and it needs to be assessed. Methods. In the current study, we investigated the morphological differences, proliferation capacity, population dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…[11][12][13] In addition, MSCs may be altered in severe aplastic anemia patients, although the results are controversial. [14][15][16] These suggested alterations in MSCs from patients with ITP or AA make it even more worthwhile to evaluate the effects of EP on healthy-donor-derived MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In addition, MSCs may be altered in severe aplastic anemia patients, although the results are controversial. [14][15][16] These suggested alterations in MSCs from patients with ITP or AA make it even more worthwhile to evaluate the effects of EP on healthy-donor-derived MSCs.…”
Section: Introductionmentioning
confidence: 99%
“…This has been examined in 5 studies using the colony forming unit-fibroblast assay ( 33 , 36 , 43 , 45 , 47 ) ( Table 6 ). Whereas the majority of studies (8/11) indicated worse proliferation and clonogenic ability of AA-MSC compared to control-MSC, others (2/11) did not observe a difference ( 25 , 47 ). In a single study the opposite result was found ( 45 ).…”
Section: Resultsmentioning
confidence: 98%
“…Qualitative methods to measure chondrogenic differentiation potential included Alcian Blue staining in addition to RT-qPCR as a quantitative measurement method. 2/4 studies found no difference in chondrogenic differentiation tendency ( 25 , 33 ) while one study observed lower chondrogenic potency in AA-MSCs ( 29 ). As indicated previously no information could be deduced from the study by Bacigalupo et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations